PERSEPSI MASYARAKAT TERHADAP APLIKASI TIKTOK SEBAGAI MEDIA MENURUNKAN TINGKAT STRES DI ERA PANDEMI COVID-19 - Kadek Ari Setia Utama Putra; Gede Wisnu Permana; Putu Yuna Sephiani; Ni Komang Sutriyanti (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2021)
Social media is a medium for socializing and communicating witheach other and is done online which is not regulated by space and time.Social media can be used as a medium to communicate privately and evenin groups, share files, videos, music, and so on. Social media which is busybeing used to reduce stress in the current pandemic era, one of which is theTikTok application. TikTok is a social media and music video platform fromChina. This application was first released in September 2016. The purposeof this research is to see the perception of the TikTok application as amedium to reduce stress levels in the Covid-19 pandemic era. Method ofcollecting data used included interviews, questionnaire questionnaires,documentation, and observation. The data obtained were analyzed usinga qualitative descriptive method. The research results are as follows 64%of people say TikTok is a medium for reducing stress. The public acceptsand rejects TikTok as the right medium to reduce stress in the Covid-19pandemic era for various reasons given. From these results it can beignored that the TikTok application influences TikTok users, both positiveand negative. This has led to various responses from the public regardingthe TikTok application.